KEPEMIMPINAN TRANSFORMASIONAL DALAM MEMBANGUN DAYA SAING DI ERA SOCIETY 5.0 - Rina Ayuni; Sulistyorini (Universitas Muhammadiyah Surabaya, 2025)
This research aims to analyze the important role of transformational leadership in building competitiveness in the Society 5.0 era. Through in-depth analysis, this research will explore how transformation-oriented leaders can create an environment that enables innovation, creativity, and effective collaboration. The method used in this research is a literature study, where reference sources or literature are obtained from national or international journals, articles, books and websites related to the topic of discussion. Through literature study, data will be interpreted in descriptive analysis. This research was carried out in the period February to May 2024. The results of the research show that the concept of transformational leadership when linked to the era of society 5.0 can be the key to increasing educational competitiveness. By utilizing technology and building strong relationships with various stakeholders, school principals can bring positive change to their educational organizations and maintain competitiveness in a dynamic environment.